Study protocol for a single-centre non-inferior double-blinded randomised controlled trial in China comparing the efficacy and safety of high-frequency irreversible electroporation with transurethral resection of the prostate in treating lower urinary tract symptoms and benign prostatic obstruction (the GIANT trial) - Rui Chen; Bi-Ming He; Zhen-Kai Shi; Hai-Feng Wang (BMJ Open)
Introduction Transurethral resection of the prostate (TURP) is the gold standard surgical treatment to lower urinary tract symptoms and benign prostatic obstruction (LUTS/BPO). Although it has been proven to have substantial efficacy in improving functional outcomes, it has shown a high incidence of complications, including transurethral resection syndrome, massive bleeding, urinary incontinence and sexual dysfunction. High-frequency irreversible electroporation (H-FIRE) is a novel non-thermal ablation technique that delivers pulsed high-voltage but low-energy electric current to the cell membrane, thereby leading to cell death. H-FIRE has been reported to be tissue-selective, which leads to fewer side effects. However, no data are available on whether H-FIRE is non-inferior compared with TURP in treating patients with LUTS/BPO regarding safety and efficacy.Methods and analysis This trial is a prospective, single-centre, randomised controlled, double-blinded and non-inferiority study in which all men with LUTS/BPO are included. This study aims to determine whether the HI-FIRE is non-inferior to TURP for achieving better functional outcomes as measured by the co-primary outcome of the change from baseline in maximal flow rate (Qmax) and the urinary symptoms by questionnaire of International Prostate Symptom Score (IPSS) scoring at 3 months after surgical treatment. The main inclusion criteria are men with prostatic volume range 30 to 100 mL, Qmax<15 mL/s and IPSS>8. A sample size of 118 participants is required, accounting for a 20% loss. All participants will be randomly allocated at a ratio of 1:1 to the H-FIRE arm (n=59) and the TURP arm (n=59). The primary outcome is to assess the change from baseline in Qmax and IPSS scoring at 3 months after surgical treatment.Ethics and dissemination Ethical approval was obtained from the ethics committee of Shanghai East Hospital, Tongji University School of Medicine, Shanghai, China. The results of the study will be disseminated and published in international peer-reviewed journals.Trial registration number ClinicalTrials.gov: NCT05306145.